2020
DOI: 10.21037/atm.2020.04.26
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 will stimulate a new coronavirus research breakthrough: a 20-year bibliometric analysis

Abstract: Background: COVID-19 is currently rampant in China, causing unpredictable harm to humans. This study aimed to quantitatively and qualitatively investigate the research trends on coronaviruses using bibliometric analysis to identify new prevention strategies.Methods: All relevant publications on coronaviruses were extracted from 2000-2020 from the Web of Science database. An online analysis platform of literature metrology, bibliographic item co-occurrence matrix builder (BICOMB) and CiteSpace software were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 22 publications
5
83
0
Order By: Relevance
“…Similar to past trends, China and the USA lead in COVID-19 scientific output (Hook & Porter, 2020;Hossain, 2020;Chahrour, Assi, Bejjani, et al, 2020). Based on a social network analysis of the current and past coronaviruses research over the past two decades, Tao et al (2020) found that while the USA has the highest level of degree centrality or has the highest impact on other countries (followed by France and the UK), research teams are relatively scattered, as demonstrated by the study's low-density global map. Bibliometric studies further identified a positive relationship between COVID-19 cases and publications; countries that were most affected by COVID-19 also produced the most scientific documents (Dehghanbanadaki, et al, 2020;Zhang, Zhao, Sun, et al, 2020), but this pattern was not always consistent.…”
Section: International Research Collaboration During Global Crisismentioning
confidence: 99%
“…Similar to past trends, China and the USA lead in COVID-19 scientific output (Hook & Porter, 2020;Hossain, 2020;Chahrour, Assi, Bejjani, et al, 2020). Based on a social network analysis of the current and past coronaviruses research over the past two decades, Tao et al (2020) found that while the USA has the highest level of degree centrality or has the highest impact on other countries (followed by France and the UK), research teams are relatively scattered, as demonstrated by the study's low-density global map. Bibliometric studies further identified a positive relationship between COVID-19 cases and publications; countries that were most affected by COVID-19 also produced the most scientific documents (Dehghanbanadaki, et al, 2020;Zhang, Zhao, Sun, et al, 2020), but this pattern was not always consistent.…”
Section: International Research Collaboration During Global Crisismentioning
confidence: 99%
“…Additionally, the choice of phrases and terms related to mental health and each of the outbreaks was exhaustive. Unlike prior analyses of the scientific literature on coronaviruses, ours did not limit to records in English ( Liu et al, 2020 ; Nowakowska et al, 2020 ; Tao et al, 2020 ; Zhai et al, 2020 ) or English and Chinese only ( Yu et al, 2020 ). We additionally extracted records from more than two databases ( Haghani et al, 2020 ; Liu et al, 2020 ) and included editorials, commentaries, letters, case reports, news, and narrative reviews ( Liu et al, 2020 ; Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published bibliometric analyses either looked at research output on various scientific and medical topics of all coronavirus outbreaks including the Severe Acute Respiratory Syndrome (SARS) and the Middle East Respiratory Syndrome (MERS) ( Bonilla-Aldana et al, 2020 ; Haghani et al, 2020 ; Liu et al, 2020 ; Tao et al, 2020 ; Yu et al, 2020 ; Zhai et al, 2020 ) or were limited to the current COVID-19 pandemic overall ( De Felice and Polimeni, 2020 ; Nowakowska et al, 2020 ). Our study is unique in that it examined an underexplored area in the COVID-19 research ( Liu et al, 2020 ), namely, the trend in mental health research, and compared the findings with two prior distinct viral outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) the study is judged to have some concerns for multiple domains in a way that substantially lowers confidence in the result. 10. Summarize patient response rates and completeness of data collection An item would be scored "0" if it was answered "No" or "Unlear"; if it was answered "Yes", then the item scored "1".…”
Section: Bias In Measurement Of Outcomesmentioning
confidence: 99%